Changes in Student Character after Distance Learning during the Covid-19 Pandemic at SMAN 15 Bulukumba - Siti Hajar; Ridha Ichwanty Sabir; Nurfadila MY.; Kaharuddin (International Journal of Qualitative Research, 2023)
This research is motivated by changes in the implementation of learning from face-to-face learning to distance learning through the use of digital technology and then changing back to face-to-face learning. Alternating the implementation of learning also influences the character of students. This research aims to provide an overview regarding changes in the character of independence, discipline, and politeness of students after distance learning during the Covid-19 pandemic at SMAN 15 Bulukumba. This research is a type of qualitative research using a case study research approach. While data collection will be carried out through observations and interviews which are then analyzed qualitatively through several activities in the form of data reduction, data presentation, and conclusion. The results of this study show that the independence of students after distance learning during the Covid-19 pandemic has increased, the discipline of students has decreased, and the politeness of students after distance learning during the Covid-19 pandemic at SMAN 15 Bulukumba has also decreased. So it can be concluded that there were changes in the character of independence, discipline, and politeness of students after distance learning during the Covid-19 pandemic at SMAN 15 Bulukumba.